2019
DOI: 10.1007/s13347-019-0341-y
|View full text |Cite
|
Sign up to set email alerts
|

Sympathy for Dolores: Moral Consideration for Robots Based on Virtue and Recognition

Abstract: This paper motivates the idea that social robots should be credited as moral patients, building on an argumentative approach that combines virtue ethics and social recognition theory. Our proposal answers the call for a nuanced ethical evaluation of humanrobot interaction that does justice to both the robustness of the social responses solicited in humans by robots and the fact that robots are designed to be used as instruments. On the one hand, we acknowledge that the instrumental nature of robots and their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…Could certain responses to social robots causally promote good or bad responses to sentient beings and so shape virtue and vice in relation to those beings, human or animal? [8] We shall mostly assume that robots do not and will not have intrinsic moral standing (question 1) (but see Sect. 9).…”
Section: Introductionmentioning
confidence: 99%
“…Could certain responses to social robots causally promote good or bad responses to sentient beings and so shape virtue and vice in relation to those beings, human or animal? [8] We shall mostly assume that robots do not and will not have intrinsic moral standing (question 1) (but see Sect. 9).…”
Section: Introductionmentioning
confidence: 99%
“…There lies an important question at the core of this issue, specifically on whether there are ways of considering the relationship between human and robot that are not slave-like. However, this falls outside the scope of the current paper (though for a beginning of an answer to this question, see [15]). In any case, this comparison illustrates the extent to which Levy's framework is unidirectional, which is further exemplified by his comparison of robot-sex with masturbation.…”
Section: Contra Instrumentalist Accountsmentioning
confidence: 88%
“…We will focus on the latter two points, but towards the end discuss their implications for design. We think it is likely that the degree of anthropomorphism [11,15,45,46] will play an important role for especially the second and third topics. This needs to be further investigated, but for the purposes of this paper we will discuss robots that tend towards the anthropomorphic rather than the more functional end-like conventional sex toys-of the anthropomorphism spectrum.…”
Section: Virtue Ethics and Social Roboticsmentioning
confidence: 99%
“…The past decade has seen a growing philosophical discussion about the moral standing of robots. For example, Bryson [6] has argued that robots are property and that they have no moral standing, whereas Gunkel [22] has argued that we consider the question regarding robot rights (for a recent overview of the discussion, see for example [7]). There is also work in the field of human-robot interaction (HRI) that acknowledges that there might be ethical problems with the way people treat robots, often framed as problems concerning anthropomorphization (e.g., [2,17,20,31]).…”
Section: Are Social Robots Kantian Dogs? Using Virtue Ethics For Thinmentioning
confidence: 99%
“…Furthermore, in robot ethics, Sparrow [32,33] has offered sophisticated arguments about what it means to take a virtue approach to robotics. Cappuccio et al [7] have argued for giving social robots moral consideration that is not based on intrinsic moral dignity and that does not attribute rights, but on the idea that relationships with robots offer to human agents opportunities to cultivate vices and virtues. And in this journal Coghlan et al [16] have reported that social robots, for example robots in the shape of animals, may affect virtue in terms of effects on the moral development of children and responses to nonhuman animals.…”
Section: Are Social Robots Kantian Dogs? Using Virtue Ethics For Thinmentioning
confidence: 99%